2022
DOI: 10.3831/kpi.2022.25.2.101
|View full text |Cite
|
Sign up to set email alerts
|

The Highest Dosage Combination Activity Screening from the Leaf Fraction of Melastoma malabathricum with Antibiotic Gentamicin and Ciprofloxacin

Abstract: Objectives: This study aims to determine the Fractional Inhibitory Concentration Index (FICI) of combinations of Melastoma malabathricum leaf fraction with ciprofloxacin or gentamicin against pathogenic bacteria, Escherichia coli, Staphylococcus aureus, and Bacillus cereus, isolated from Diabetic Foot Ulcer (DFU) patients. Methods: We tested concentrations of 45%, 55%, 65%, and 75% of gentamicin and ciprofloxacin using dilution and agar diffusion methods. The combination of M. malabathricum leaf extract with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…This study reinforced the use of plants containing gallic acid in formulation development, specifically focusing Melastoma malabathricum [13]. Sari et al, 2022 showed the synergistic effects of EAF and Gentamicin combination, which acted as an effective antibiotic against Bacillus cereus, Escherichia coli, and Staphylococcus aureus. Therefore, this current study aims to develop and validate an analytical method for quantifying gallic acid levels within SNEDDS formulation, a combination of Melastoma malabathricum leaves EAF and Gentamicin, which is promising for the effective treatment of chronic wounds such as DFU.…”
Section: Introductionmentioning
confidence: 52%
See 2 more Smart Citations
“…This study reinforced the use of plants containing gallic acid in formulation development, specifically focusing Melastoma malabathricum [13]. Sari et al, 2022 showed the synergistic effects of EAF and Gentamicin combination, which acted as an effective antibiotic against Bacillus cereus, Escherichia coli, and Staphylococcus aureus. Therefore, this current study aims to develop and validate an analytical method for quantifying gallic acid levels within SNEDDS formulation, a combination of Melastoma malabathricum leaves EAF and Gentamicin, which is promising for the effective treatment of chronic wounds such as DFU.…”
Section: Introductionmentioning
confidence: 52%
“…Hainil et al, 2023 detected that EAF showed an inhibitory effect of 92%, compared to the 96% observed in ascorbic acid. In a separate study by Apridamayanti et al, 2022, the preparation of nanocream containing EAF indicated an antioxidant capacity of 1444.157±15.538 μg/ml as measured by the FRAP method [5,8,9].…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation